Mobilizing Metacognitive Strategies Through Zoom for EFL Classrooms: An Innovative Practice Amidst Covid 19 - Luís Miguel Cardoso; Nur Aeni; Muthmainnah Muthmainnah (Journal of Language Learning and Assessment, 2023)
Purpose The goal of this study is to investigate student’s metacognitive skill online learning via Zoom app during the Covid-19 pandemic.  The online lectures are the primary method of instruction. Lecturers and students mostly used Zoom apps to deliver lectures amidst Covid 19 pandemic. Methodology This study used quantitative research and the data collection was conducted through questionnaires on student’s metacognitive skill spread by google form to the EFL students at a private university completed a questionnaire via Google Form. There were 24 students in total. Results/Findings This study results showed students perception online learning via Zoom was used its highly involved student’s metacognitive skill. It is considered as an effective platform to enhance students’ interactions and engagement. Implications This study result in Zoom class lecturer develops metacognitive strategies to support higher order thinking skill and 21th century skill of students. This result of the study can be used by other educators in mobilizing metacognitive strategies.